STUDI EMISI CO2AKIBAT KEBAKARAN HUTAN DI PROVINSI RIAU (STUDI KASUS DI KABUPATEN SIAK) - Nasution, A.Z. (Bumi Lestari, 2013)
Abstract This research was aimed to analyze the CO 2 emissions due to forest fires that occurred in Siak Regency, Riau Province Indonesia in 2010 and to analyze the probability of forest fire occurrence in Siak Regency using the available data. Fire and CO2 emissions in the area of plantation forests are greater than in the area of natural forests. The amount of CO 2 emissions due to forest fires in 2010 varied between 107.260 Ton CO2 yr-1 in natural forests and 151.600 Ton CO2 yr-1 in plantation forests. The amount of CO 2 emissions due to forest fires in the peat land was 2.176 Ton CO2 yr-1. This value is mainly depending on the extent of the burned area in the year of 2010. Results of the logistic regression show the forest fires are more likely to occur in degraded forests.
Keywords: Key words: Forest fires, CO 2 emissions, fire occurrence, Riau, Siak.